2023
DOI: 10.3389/fpsyt.2023.1271152
|View full text |Cite
|
Sign up to set email alerts
|

5-MeO-DMT for post-traumatic stress disorder: a real-world longitudinal case study

Anya Ragnhildstveit,
Ryan Khan,
Paul Seli
et al.

Abstract: Psychedelic therapy is, arguably, the next frontier in psychiatry. It offers a radical alternative to longstanding, mainstays of treatment, while exciting a paradigm shift in translational science and drug discovery. There is particular interest in 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT)—a serotonergic psychedelic—as a novel, fast-acting therapeutic. Yet, few studies have directly examined 5-MeO-DMT for trauma- or stress-related psychopathology, including post-traumatic stress disorder (PTSD). Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, survey studies demonstrate that the 5‐MeO‐DMT‐induced mystical experience is associated with improvements in symptoms of depression, 47 , 50 post‐traumatic stress disorder (PTSD), 47 , 51 , 52 and anxiety. 47 , 50 This indicates that 5‐MeO‐DMT could alleviate psychiatric mood‐related comorbidities that are highly prevalent in AUD.…”
Section: Potential Therapeutic Mechanisms Of Action Of 5‐me...mentioning
confidence: 99%
“…Furthermore, survey studies demonstrate that the 5‐MeO‐DMT‐induced mystical experience is associated with improvements in symptoms of depression, 47 , 50 post‐traumatic stress disorder (PTSD), 47 , 51 , 52 and anxiety. 47 , 50 This indicates that 5‐MeO‐DMT could alleviate psychiatric mood‐related comorbidities that are highly prevalent in AUD.…”
Section: Potential Therapeutic Mechanisms Of Action Of 5‐me...mentioning
confidence: 99%
“…Reckweg et al presented a phase 1 dose-ranging study to assess the safety and psychoactive effects of a vaporized 5-MeO-DMT formulation in healthy volunteers (Reckweg et al, 2021). Ragnhildstveit et al presented a longitudinal case study of a patient who successfully self-medicated her PTSD with 5-MeO-DMT (Ragnhildstveit et al, 2023). Concerning DMT, Timmermann et al found 'a striking similarity between DMT-induced near-death experiences and actual near-death experiences (NDEs) (Timmermann et al, 2018).…”
Section: Alternatives To Ketaminementioning
confidence: 99%
“…A recent narrative review by Ermakova et al provided a look into the history of the substance, its pharmacology, pharmacokinetics, effects, drug interactions, and toxicology (Ermakova et al, 2021). Ragnhildstveit et al presented a longitudinal case study of a patient who successfully self-medicated her PTSD with 5-MeO-DMT (Ragnhildstveit et al, 2023).…”
mentioning
confidence: 99%